ISO 9000 quality systems handbook using the standards as a framework for business improvement - Hoyle, David (Amsterdam ; Boston ; London : Butterworth-Heinemann, 2009)
Whether you are establishing a quality management system for the first time or improving your existing system, this best-selling guide to effective quality management using the ISO 9000 family of standards as a framework for business process management (BPM) and improvement is an essential addition to your quality bookshelf. For newcomers to the field and those needing a refresh on the fundamental principles, quality expert David Hoyle covers the crucial background including the importance and implications of quality system management, enabling those seeking ISO 9001 certification to take a holistic approach that will bring about true business improvement and sustained success. Packed with insights into how the standard has been used, misused and misunderstood, ISO 9000 Quality Systems Handbook will help you to build an effective management system, help you decide if ISO 9001 certification is right for your company and gently guide you through the terminology, requirements and implementation of practices to enhance performance. With chapter headings matched to the structure of the standard and clause numbers included for ease of reference, each chapter now also begins with a preview to help you decide which to study and which to skip. The book also includes essential concepts and principles, important issues to be understood before embarking upon implementation, different approaches that can be taken to achieving, sustaining and improving quality, and guidance on system assessment, certification and continuing development. Clear tables, summary checklists and diagrams make light work of challenging concepts and downloadable template report forms, available from the book's companion website, take the pain out of compiling the necessary documentation. Don't waste time trying to achieve certification without this tried and trusted guide to improving your business-let David Hoyle lead you towards a better quality management system and see the difference it can make to your processes and profits! * Reduce your need for expensive training and consultancy services with this authoritative, clear and unambiguous guide to quality management from one of the world's foremost experts on the ISO 9000 family of standards. * Develop a process based management system that enables your organization to satisfy its customers and other stakeholders as well as conform to ISO 9001:2008 with hard-won information from quality auditors and industry experts. * Explains the concepts and requirements with compelling case studies, summaries of the essential learning points and check lists to ensure certification is achieved without delays caused by oversights. Downloadable template report forms also available on the book's companion website!
Putting ISO 9000 in context -- Defining and characterizing quality -- The importance and role of stakeholders -- Anatomy of the standards -- A practical guide to using these standards -- A flawed approach -- A systems approach -- A process approach -- A behavioural approach -- Establishing a quality management system -- Documenting a quality management system -- Document control -- Management commitment -- Customer focus -- Quality policy -- Quality objectives and planning -- Responsibility, authority and communication -- Management review -- Determining and providing resources -- Human resources -- Infrastructure -- Work environment -- Planning product realization processes -- Customer-related processes -- Design and development -- Purchasing -- Production and service provision -- Monitoring, measurement, analysis and improvement processes -- Customer satisfaction -- Internal audit -- Measurement and monitoring of products and processes -- Control of monitoring and measuring equipment -- Control of nonconforming product -- Analysis of data -- Continual improvement -- Corrective action -- Preventive action -- Self assessment -- System certification -- Beyond ISO 9001 certification -- Related web sites -- Related standards -- Glossary -- Index.
Previous ed.: 2006.
Includes bibliographical references and index.
Includes web resources.
Keywords: ISO 9000 Series Standards -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc